Outcome of two knots tension band wiring (TBW) in Mayo type-IIA olecranon fracture (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Olecranon fracture is relatively common and accounts for approximately 40% of elbow joint fractures. It is an intra-articular fracture, so the aim of treatment is anatomic reduction, stable fixation and early mobilization. Tension band wiring (TBW) may be a popular and widely practiced method using either single knot or two knots techniques. Now two knots TBW are widely accepted by AO foundation as well as various countries. But single knot technique is commonly practiced in Bangladesh. The present study was done to see the clinical, radiologi- cal and functional outcome of two knots Tension band wiring (TBW) in Mayo type IIA olecranon fracture. This observational study was carried out by the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh. A total of 32 patients with Mayo type IIA olecranon fractures were treated with two knots TBW, out of which 30 cases had completed at least 24 weeks of follow-up and analyzed for final functional outcome with Mayo Elbow Performance Score (MEPS). The mean age was 32.58±14.21 years and the male to female ratio was 2.6:1. The mean radiological union time was 8.15±2.25 weeks. In 6 (18.75%) cases, it took 6 weeks, in 18 (56.25%) cases, it took 8 weeks and in 8 (25.0%), it took 12 weeks. Complications were found in 21.9% of patients. At first follow-up after the operation showed that 21 (70.0%) had moderate pain and the final follow-up showed 21 (70.0%) had no pain. The mean arc of elbow motion at first follow-up and final follow-up were 61.090±16.2340 and 122.820±15.2870, respectively. The mean functional score at 1st follow-up was 6.75±5.63 and the last follow-up was 24.76±1.69. The mean total Mayo Elbow Performance Score (MEPS) scores at first and last follow-up were 40.65±14.48 and 94.13±8.35, respectively. Excellent and good outcomes were found among 21 (70.0%) and 9 (30.0%) patients, respectively. Two knots TBW technique is safe regarding overall complication rate, pain status and excellent outcome.BSMMU J 2022; 15(2): 90-95